INTEGRATING ARTIFICIAL INTELLIGENCE-BASED LEARNING MEDIA IN ENGLISH LANGUAGE TEACHING AT THE ELEMENTARY SCHOOL LEVEL - Rina Husnaini Febriyanti; Hanna Sundari (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
ABSTRACTThis study presents a community engagement initiative conducted at SDN Citayam, an elementary school located in Kampung Baru RT 03/05, Desa Citayam, Kecamatan Tajur Halang, Kabupaten Bogor, West Java. The primary objective of this initiative was to provide training to educators on the implementation of Artificial Intelligence-based learning media in English language teaching. The activities encompassed both theoretical and practical aspects, elucidating the application and optimization of Artificial Intelligence-based learning media within the context of English language instruction. The participants involved in this community engagement program were the teachers teaching at SDN Citayam. The methodology employed for the training program was Community Language Learning, which fostered a collaborative environment for discussion, knowledge sharing, and reflection on the theoretical concepts and practical implications in the teaching process. This community engagement initiative was conducted during the second semester of the Academic Year 2022/2023. Keywords: Learning Media, Artificial Intelligence, English Language Teaching